Early human herpes virus type 6 reactivation in umbilical cord blood allogeneic stem cell transplantation. Issue 11 (1st November 2016) - Cirrone, Frank; Ippoliti, Cindy; Wang, Hanhan; Zhou, Xi Kathy; Gergis, Usama; Mayer, Sebastian; Shore, Tsiporah; van Besien, Koen
Abstract: Human herpes virus type 6 can reactivate in patients after allogeneic stem cell transplantation and has been associated with serious sequelae such as delayed engraftment and an increased risk of developing acute graft-versus-host disease (GVHD). This study investigated human herpes virus type 6 (HHV-6) reactivation within 60 days of transplantation in stem cell transplants utilizing single umbilical cord blood, double umbilical cord blood, or umbilical cord blood plus haploidentical stem cells. Of 92 patients, 60 (65%) had HHV-6 reactivation. Reactivation was not significantly influenced by any patient characteristics, disease characteristics, or by stem cell source (umbilical cord blood only versus haploidentical plus umbilical cord blood). We did not observe any impact of HHV-6 reactivation on neutrophil or platelet count recovery or on relapse-free survival. HHV-6 reactivation was associated with subsequent development of prerelapse acute GVHD (HR = 3.00; 95% CI, 1.4 to 6.4; p = 0.004).